PENERJEMAHAN PRAGMATIK TEKSTUAL DALAM PENGAJARAN BIPA - Nana Raihana Askurny (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Study of teaching learning of BIPA (Bahasa Indonesia untuk Penutur Asing) or Indonesian Language for Non Native Speakers becomes a specific and identical field in education. Balai Bahasa Medan operates BIPA class since 2009 until today; this practically shows that translation method is undeniable. The researcher and also as BIPA teacher found that process of translating applied consciousness whether by the students and also by the teacher. Translation happened from the source language (Indonesia) to English as education language practiced by the teacher, and form his mother language to Indonesian language, practiced by the student. The data of this research is words, phrases, and clauses, they are observed, collected, and analyzed. Finally, its concluded that pragmatic translation was applied by teacher and students, and specifically occurred by words, phrases, and clauses which are different colucution, routine personal pronoun, and pragmatic translation in the matter of diction.